INTRAPERSONAL COMMUNICATION AND MUSLIM IDENTITY IN THE DIASPORA: A NARRATIVE STUDY OF THE FILM RENTANG KISAH - Fatmawati (Pascasarjana Universitas PTIQ Jakarta, 2025)
This study aims to determine how to analyze the narrative at the beginning, middle, and end of a film. This research uses a qualitative approach with narrative analysis methods. Primary data sources were obtained from scene clips, dialogue, and monologues of the main characters in the film. Secondary data were taken from Gita Savitri's book Rentang Kisah, a literature on intrapersonal communication and the Muslim diaspora. The results show that the film Rentang Kisah depicts how the Muslim minority can become a force in shaping the personality of Muslims in Germany. Deciding to wear the hijab while in Germany, and someone experiencing religious unrest, ultimately finds a bright spot and chooses Islam as their religion and recites the two sentences of the shahada. This research can generate a new conceptual model of the stages of intrapersonal communication in identity formation, reflected through narrative media film, which can be used as a basis for further research in media studies or personal communication. The findings of this narrative analysis can also serve as a reference for filmmakers, screenwriters, and filmmakers who want to depict the journey of Muslim identity authentically and in-depth.